PERILAKU KONSUMSI SUSU PADA WANITA DEWASA DI JAKARTA TIMUR - Retnaningsih Retnaningsih; Cesilia Meti Dwiriani; Ary Kurniati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2008)
This study was aimed to analyze consumers and milk product characteristics consumed by adult women living in East Jakarta. The study was applied to 300 out of 304,962 households having telephone number listed in “2001-2002 Telephone Registered Book”. The samples were women aged 21-55 years old and currently consume milk, i.e. drinking milk at least one time in the last one month. The data were gathered using telephone interview. Almost 80% of the samples were 21-45 years old, half of the samples had middle level of educational background (SMP/SMU) were gathered using telephone interview. Almost 80% of the samples were 21-45 years old, half of the samples had middle level of educational background (SMP/SMU). Half of the samples had monthly income range from 299,000 – 1,105,000 rupiahs and almost 60% having milk expenditure less than 40,000 rupiahs monthly. Kinds of milk consumed by adult women were powder (full cream, skim or calcium milk). Supermarket was the place chosen by almost 90% consumers to buy milk. Nutrition value was the main attribute when samples choose and buy the milk. Almost all samples drink milk for healthy reason. Estimated the average of calcium intake from milk is more than 35% of Indonesian calcium adequacy level. The data showed that milk consumed were significantly related to level of education, monthly income and monthly milk expenditure.